A case of paroxysmal neck swelling - Harsoor, Aishwarya Rani; Muralikrishnan, P. (International Journal of Contemporary Pediatrics, 2025)
Internal jugular vein ectasia is a rare congenital condition that often presents with neck swelling during straining in children. We reported a 5-year-old female with paroxysmal neck swelling noticed during activities like coughing or shouting. Imaging confirmed transient internal jugular vein ectasia. The patient was managed conservatively. Conservative management is preferred in asymptomatic cases, with surgical intervention reserved for complications.